Warm Compress Therapy to Resolved Acute Pain Nursing Problems: A Case Study - Kushariyadi; Maulida, Rifa Refina Ria; Ridla, Akhmad Zainur; Candra, Eka Yufi Septriana (Al-Hijrah Indonesia, 2023)
Background: the application of complementary therapies in hospitals is still not optimal. The limitations of the application of nursing interventions are caused by the factor of applying therapy by nurses to patients and education related to therapy to patients is still rarely done. Nurses are still focusing on conventional treatment with pharmacological therapies such as analgesic drugs to relieve pain, while warm compress therapy is still not prioritized. The application of warm compress therapy in the inpatient room of Gardena dr. Soebandi General Hospital Jember to overcome acute pain nursing problems in patients is still rare. Aims: evaluate warm compress interventions in patients with acute pain nursing problems. Method: type of research case study using nursing care method. The sample was a patient treated in the Gardena room of dr. Soebandi General Hospital Jember with acute pain nursing problems. Patients are given nursing intervention in the form of warm compress therapy for 15-20 minutes for 3 days, from January 16 to 18, 2023. Nursing intervention is given through the nursing process, which is teaching directly to patients and families with the right and appropriate techniques to adjust the patient's condition. Results: the provision of nursing interventions in the form of warm compresses can overcome acute pain nursing problems. This is shown by the improvement of the patient's condition that complaints of pain, grimacing and restlessness decrease and sleep patterns improve. Patients can do the therapy independently properly and correctly. Conclusion: warm compress therapy is effective in overcoming acute pain nursing problems.